2016
DOI: 10.1007/s10753-016-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

1, 8-Cineol Protect Against Influenza-Virus-Induced Pneumonia in Mice

Abstract: 1,8-Cineol is a major monoterpene principally from eucalyptus essential oils and has been shown to exert anti-inflammatory, antiviral, and inhibitory of nuclear factor (NF)-kB effect. In the present study, we evaluated the effect of 1,8-cineol on mice infected with influenza A virus. We found that 1,8-cineol protects against influenza viral infection in mice. Moreover, 1,8-cineol efficiently decreased the level of IL-4, IL-5, IL-10, and MCP-1 in nasal lavage fluids and the level of IL-1β, IL-6, TNF-α, and IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 52 publications
4
50
0
9
Order By: Relevance
“…For eucalyptol treatment, the dosages (30, 100, 300, or 600 mg·kg −1 , i.p.) were based upon previous studies tested in rodents (Caceres et al, ; Li et al, ). Eucalyptol was applied 1 hr before MSU injection and 5, 23, and 47 hr after MSU injection for a total of four times (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For eucalyptol treatment, the dosages (30, 100, 300, or 600 mg·kg −1 , i.p.) were based upon previous studies tested in rodents (Caceres et al, ; Li et al, ). Eucalyptol was applied 1 hr before MSU injection and 5, 23, and 47 hr after MSU injection for a total of four times (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Eucalyptol is widely used as a treatment option for symptoms of the common cold, respiratory infections, pancreatitis, and colitis and for pain relief (Juergens, ; Seol & Kim, ). Studies have demonstrated that eucalyptol possess antioxidant activity, can suppress LPS‐induced IL‐1β and NO production, and reduce LPS‐induced NF‐κB activation (Kennedy‐Feitosa et al, ; Kim, Lee, & Seol, ; Li et al, ; Seol & Kim, ). Eucalyptol also inhibits TRPA1 channels and diminishes pain elicited by application of TRPA1 channel agonists to human skin (Takaishi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This compound only reached 0.41% in marjoram essence analysed here. So, an anti-anxiety (Kim, Seo, Min, Park, & Seol, 2014), antimicrobial with application as natural preservative in food packaging (Taqi, Askar, Mutihac, & Stamatin, 2013), anti-inflammatory, antiviral or inhibitory of nuclear factor (NF)-kB effect (Li et al, 2016) could be expected with marjoram essence due to high 1,8-cineol (59.59%) content. Our results are in agreement with the percentages obtained from 20 samples of T. mastichina essential oils (1,8-cineol 56.80-69.60%) from Spain (Delgado et al, 2014), and according with ISO quality standards (Table 4) of T. mastichina (Mendez-Tovar, Novak, Sponza, Herrero, & Asensio-S-Manzanera, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of acute lung injury (IPA) induced by LPS, BALB / C, mice were subjected to single dose pre-treatment via intraperitoneal injection with 400 mg/kg Eucalyptol, where it caused a reduction in NF-κB expression and, consequently, cytokines and proteinases [47]. Similar results in NF-kB suppression, compared to Eucalyptol treatment, were also observed in the IPA model caused by cigarette smoke [41] and pneumonia model caused by influenza virus infection (IFV), where BALB / C mice received oral treatment at 120 mg/kg, two days prior to the viral exposure [48]. In addition, Greiner and collaborators [49], suggested a novel mode of NF-kB blockade through inhibition of nuclear translocation by the nuclear factor kappa B alpha inhibitor (IκBα) and increased levels in response to treatment with Eucalyptol after stimulation with LPS.…”
Section: Transcription and Expression Of Cytokinesmentioning
confidence: 63%